An Advanced Technique to Evaluate the Electrochromic Performances of NiO Films by Multi-Cycle Double-Step Potential Chronocoulometry. Issue 10 (1st January 2016) - Zhou, KaiLing; Wang, Hao; Zhang, YongZhe; Liu, JingBing; Yan, Hui
Abstract : NiO films with amorphous and crystalline structure are prepared via sol-gel method. The electrochromic performances are evaluated in a KOH electrolyte by cyclic voltammetry (CV), which demonstrates that the crystalline NiO thin film has excellent stability and durability compared with the amorphous film. Meanwhile, the unique method of multi-cycle double-step potential chronocoulometry (MDPC) is firstly employed to analyze the electrochromic performance of the NiO films. It shows that the cyclic tendency obtained from MDPC is consistent with the CV evolutions. The relationship between charge densities and cycles can be directly obtained by MDPC, consequently, the reversibility of films can be directly evaluated by the ratio of the extracted/inserted charges. As a primary advantage, the response charges obtained by MDPC technique can be divided into three parts including Faradic charges ( Qf ) associated with redox activity leading to chromic change, the capacitive charges ( Qdl ) corresponding to charging and discharging of electrode-electrolyte double-layer capacitor, and parasitic charges ( Qads ) consumed by electrolysis of adsorbed species. The electrochromic mechanism of NiO films are further explored by analyzing the cycle dependence of Qf and Qads evolutions. It adequately supports that MDPC has significant advantage to analyze the electrochromic performance and mechanism of electrochromic materials.